2012
DOI: 10.1111/j.1439-0531.2012.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neurotrophin‐4 (NT‐4) in Ejaculated Bull Spermatozoa and its Effect on Spermatozoa Mitochondrial Activity

Abstract: Recently, we demonstrated that two members of neurotrophins, nerve growth factor and brain-derived neurotrophic factor, and two types of receptor, tyrosine kinase A (TrkA) and tyrosine kinase (TrkB), exist in ejaculated bull spermatozoa, and play a crucial role in the normal function of spermatozoa. Neurotrophin-4 (NT-4) is another neurotrophic factor that signals predominantly through the TrkB receptor tyrosine kinase, and no reports of detection of NT-4 in spermatozoa have been published. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Both the mRNAs encoding BDNF, NT4 and TRKB and the corresponding proteins have been detected in ejaculated bull sperm. The BDNF protein was found in the head, neck and tail of the sperm cells, whereas NT4 was localized in the equatorial segment and the mid-section of the spermatozoa and TRKB was strongly localized in the acrosome (Li et al 2012, Wang et al 2013.…”
Section: The Roles Of Neurotrophins In Testicular Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the mRNAs encoding BDNF, NT4 and TRKB and the corresponding proteins have been detected in ejaculated bull sperm. The BDNF protein was found in the head, neck and tail of the sperm cells, whereas NT4 was localized in the equatorial segment and the mid-section of the spermatozoa and TRKB was strongly localized in the acrosome (Li et al 2012, Wang et al 2013.…”
Section: The Roles Of Neurotrophins In Testicular Developmentmentioning
confidence: 99%
“…Interestingly, BDNF can increase the secretion of insulin and leptin in ejaculated sperm, and treatment with exogenous BDNF for 2 h affects sperm apoptosis and viability. Moreover, both BDNF and NT4 have been shown to regulate mitochondrial activity in sperm (Li et al 2012, Wang et al 2013. A clinical study has shown that the levels of BDNF mRNA in the sperm and BDNF protein in the seminal plasma of a group of oligoasthenozoospermic men were lower than those in a fertile group, indicating that the decreases in the abundance of BDNF and its mRNA transcript may be associated with pathogenesis in some types of male infertility (Zheng et al 2011).…”
Section: The Roles Of Neurotrophins In Testicular Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the mRNAs encoding BDNF and neurotrophic tyrosine kinase receptor, type 2 (Ntrk2) and the corresponding proteins have been detected in ejaculated bull sperm. The BDNF protein was found in the head, neck, and tail of the sperm cells, whereas Ntrk2 was strongly localized in the acrosome (Li et al, 2012, Wang et al, 2013). Furthermore, BDNF/ Ntrk2 signaling affected sperm viability, mitochondrial activity, and apoptosis (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The truncation containing the mature βNGF was not detected in our study but βNGF contributed to the enrichment of BDNF signaling pathway. BDNF (brain-derived neurotrophic factor) affects sperm mitochondrial activity and apoptosis, as well as sperm viability [113,114]. Enrichment of the calcium signaling pathway, electron transport chain and thermogenesis linked to the seminal plasma profile of LF bulls supports the evidence that sperm membrane from these individuals have lower resistance to cryoinjuries due to premature activation of capacitation and metabolic processes.…”
Section: Discussionmentioning
confidence: 85%